PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA - , EKAWATI JATI W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to empirically examine the effect of audit quality on earnings management in manufacturing companies that go public in the Indonesia Stock Exchange (IDX) 2009-2013, by firm size, growth prospect, leverage, operating cash flow, and operating cycle as a control variable . Earnings management as measured by discretionary accruals (DA) based on the Modified Jones Model and audit quality is measured using size Public Accounting Firm, Public Accounting Firm Industry Specialization, and audit tenure. The sampling method in this study is the purposive sampling technique was used and the sample companies listed in Indonesia Stock Exchange (IDX) 2009-2013. The result of this study showed that that public accounting firm size (SIZE), the Office of the Public Accounting industry specialization (SPEC) and audit tenure (tenure) has no effect on the practice of earnings management as measured by discretionary accruals (DA), it can be concluded that the hypothesis is not declared supported. Results of tests performed on the control variables obtained that firm size (FIRM) negative effect on earnings management as measured by discretionary accruals (DA). Growth prospect (GROW) positive effect on discretionary accruals (DA). Leverage (LEV) positive effect on earnings management as measured by discretionary accruals (DA). Operating cash flow (OCF) and the operating cycle (OC) has no effect on earnings management as measured by discretionary accruals (DA).